Paper-Plastic Hybrid Microfluidic Device for Smartphone-Based Colorimetric Analysis of Urine - Jalal, Uddin M; Jin, Gyeong Jun; Shim, Joon S (Analytical chemistry (Washington), 2017)
In this work, a disposable paper-plastic hybrid microfluidic lab-on-a-chip (LOC) has been developed and successfully applied for the colorimetric measurement of urine by the smartphone-based optical platform using a "UrineAnalysis" Android app. The developed device was cost-effectively implemented as a stand-alone hybrid LOC by incorporating the paper-based conventional reagent test strip inside the plastic-based LOC microchannel. The LOC device quantitatively investigated the small volume (40 μL) of urine analytes for the colorimetric reaction of glucose, protein, pH, and red blood cell (RBC) in integration with the finger-actuating micropump. On the basis of our experiments, the conventional urine strip showed large deviation as the reaction time goes by, because dipping the strip sensor in a bottle of urine could not control the reaction volume. By integrating the strip sensor in the LOC device for urine analysis, our device significantly improves the time-dependent inconstancy of the conventional dipstick-based urine strip, and the smartphone app used for image analysis enhances the visual assessment of the test strip, which is a major user concern for the colorimetric analysis in point-of-care (POC) applications. As a result, the user-friendly LOC, which is successfully implemented in a disposable format with the smartphone-based optical platform, may be applicable as an effective tool for rapid and qualitative POC urinalysis.